2002
DOI: 10.1007/s00232-001-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Sodium Channel (Nax) Activated by Strong Depolarization of Xenopus Oocytes

Abstract: Short (<1 sec) duration depolarization of Xenopus laevis oocytes to voltages greater than +40 mV activates a sodium-selective channel (Na(x)) with sodium permeability five to six times greater than the permeability of other monovalent cations examined, including K+, Rb+, Cs+, TMA+, and Choline+. The permeability to Li+ is about equal to that of Na+. This channel was present in all oocytes examined. The kinetics, voltage dependence and pharmacology of Na(x)distinguish it from TTX-sensitive or epithelial sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
3
6
2
1
Order By: Relevance
“…In the present thesis work, this channel was demonstrated to be upregulated during apoptosis, and in previous studies it is upregulated after a prolonged depolarisation. Both our apoptotic-induced Na + currents reported here and the Na x current reported by others are blocked by a high concentration of lidocaine (reported in paper II) (Baud et al, 1982;Charpentier, 2002;Vasilyev et al, 2002). By using miRNA to suppress the Na + current upregulated during apoptosis we could identify the channel conducting the Na + current as a SCN2A ortholog.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In the present thesis work, this channel was demonstrated to be upregulated during apoptosis, and in previous studies it is upregulated after a prolonged depolarisation. Both our apoptotic-induced Na + currents reported here and the Na x current reported by others are blocked by a high concentration of lidocaine (reported in paper II) (Baud et al, 1982;Charpentier, 2002;Vasilyev et al, 2002). By using miRNA to suppress the Na + current upregulated during apoptosis we could identify the channel conducting the Na + current as a SCN2A ortholog.…”
Section: Discussionsupporting
confidence: 61%
“…The voltage-gated Na channel described in paper II, and which identity is revealed in paper III, is most likely responsible for causing the Na x current that has previously been described in X. laevis oocytes (Baud et al, 1982;Vasilyev et al, 2002), not to be confused with human SCN7A which also has been called Na x . The Na x current activates at positive voltages and does not inactivate.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Na + channels activated by ATP [37], and 4. Na x channels activated by a positive voltages [32], [38]. Even though we have not tested for intracellular acidification and NH 4 + , we found that Na x is a strong candidate for the channel described in the present investigation.…”
Section: Discussioncontrasting
confidence: 44%
“…Xenopus oocytes express several types of endogenous channels that may conduct Na ϩ (15)(16)(17)(18). To exclude the possibility that the observed increase in whole cell currents by extracellular Zn 2ϩ was due to activation of an endogenous channel, we examined the effect of 100 M ZnCl 2 on the whole cell currents in H 2 O-injected oocytes.…”
Section: External Zn 2ϩ Activates ␣␤␥ Menac Expressed In Xenopusmentioning
confidence: 99%